Synthesis of acrylate-based polymeric and polymerisable surfactants and their application in the emulsion polymerisation of styrene - Tichagwa, Lilian M. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2006.